"Libraries model sustainability": The results of an OCLC survey on library contributions to the Sustainable Development Goals1. (June 2023) - Connaway, Lynn Silipigni; Doyle, Brooke; Cyr, Christopher; Gallagher, Peggy; Cantrell, Joanne
A survey of more than 1700 library staff worldwide identifies how libraries contribute to five of the United Nations Sustainable Development Goals. The similarities between academic and public libraries' adoption, contribution, and use of the Sustainable Development Goals are reported. The results indicate that library staff do substantial work around all five of the selected Sustainable Development Goals. Sometimes the activities are a result of integrating the Sustainable Development Goals into strategic planning, but at other times the activities are a result of programming that library staff undertake as part of their mission. The majority of the respondents have not incorporated the Sustainable Development Goals into their strategic planning. However, the libraries' support of the Sustainable Development Goals is demonstrated by the activities the library staff are engaged with and the respondents' comments. The activities identified here can be used to inform library strategic planning and to help library staff maximize their library's impact on sustainable development.